Analisis Hubungan dan Implikasi Nilai-Nilai Karakter Dalam Kompetensi Inti - Hakim, Ilham Faiqul; Naili, Maftuhah; Sabrina, Adinda; Anja, Isna; Iqbal, Muhammad (Tarqiyatuna: Jurnal Pendidikan Agama Islam dan Madrasah Ibtidaiyah, 2024)
This study aims to analyze the relationship and implications of character values in core competencies (IC), basic competencies (KD), learning outcomes (CP), indicators of competency achievement (GPA), and learning objectives in the context of Islamic religious education. The literature research method for the theme "Analysis of the Relationship and Implications of Character Values in Core Competencies" involves data collection through literature study, data analysis with a qualitative approach, and method validation with reference to the framework that has existed in previous research. The study shows that: 1) KD is the learning outcome of students, IC is the main ability in social life, CP is what students are expected to master, and Competency Achievement Indicators are KD assessments, all important in achieving Learning Objectives, 2) Core Competencies and Basic Competencies as a foundation, as well as teachers who understand well KI, KD, and Indicators to design effective learning and in accordance with learning objectives, 3) Character values are important aspects of education instilled in students through KI, KD, CP, GPA, and learning objectives, focusing on positive values such as honesty, discipline, cooperation, responsibility, respect for diversity, creativity, discipline, respect, and the desire to produce ethical and competent individuals in facing life's challenges, 4) Examples of KD, KI, CP, Good and correct GPA. The implication of this study is that increasing the understanding and application of character values in Core Competencies can help shape more qualified and ethical individuals in society.